1993
DOI: 10.1172/jci116503
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell adhesion in real time. Measurements in vitro by tandem scanning confocal image analysis.

Abstract: Real time measurements of cell-substratum adhesion in endothelial cells were obtained by tandem scanning confocal microscopy of sites of focal contact (focal adhesions) at the abluminal cell surface. Focal contact sites were sharply defined (low radiance levels) in the living cell such that the images could be enhanced, digitized, and isolated from other cellular detail. Sites of focal contact are the principal determinant of cell-substratum adhesion. Measurements of (a) the focal contact area and (b) the clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 36 publications
2
64
1
Order By: Relevance
“…f 0 is a reference frequency taken to be 1 Hz pN. The adhesion density at the cell surface is typically d = 0.15 adhesions/µm 2 (Davies et al, 1993(Davies et al, , 1994. If 20 to 30% of the bead is embedded in the membrane, the bead surface area available for binding to membrane proteins is 0.8 − 1.2πr 2 , where r is the bead radius, and the number of cell-bead adhesions would be ∼ 0.8−1.2πr 2 d. This yields a typical force per adhesion of F ext = F bead /πr 2 d ≈ 600 pN.…”
Section: Resultsmentioning
confidence: 99%
“…f 0 is a reference frequency taken to be 1 Hz pN. The adhesion density at the cell surface is typically d = 0.15 adhesions/µm 2 (Davies et al, 1993(Davies et al, , 1994. If 20 to 30% of the bead is embedded in the membrane, the bead surface area available for binding to membrane proteins is 0.8 − 1.2πr 2 , where r is the bead radius, and the number of cell-bead adhesions would be ∼ 0.8−1.2πr 2 d. This yields a typical force per adhesion of F ext = F bead /πr 2 d ≈ 600 pN.…”
Section: Resultsmentioning
confidence: 99%
“…The focal adhesion sizes had a wide size distribution (between 0.3-15 mm), which can be interpreted as being representative of the constant dynamic remodeling of all adhesion sites produced. 16 For the rougher surface of TS, the cell morphology indicated that the topography impinged significantly upon cell spreading with the cell periphery often aligned to the rough ''basketweave'' topography, producing a jagged polygonal cell periphery. Fluorescence indicated considerable interaction; however, quantitatively the cell area was significantly different to that of cells on SS, but not to TE or NE.…”
Section: Discussionmentioning
confidence: 95%
“…An intensity threshold was determined to define the contact/adhesion area. The threshold intensity I thresh was derived from equation 1 by setting the threshold membrane-to-substrate distance at 40 nm [25][26][27][28] for a wavelength of λ 1 = 593 nm or λ 2 = 546 nm and using the minimum and maximum intensities I m and I M on each cell image [29]. This is a semi-quantitative method [25,29] which distinguishes between adherent and nonadherent parts of the cell membrane.…”
Section: Data Analysis Of Ricm Imagesmentioning
confidence: 99%
“…To identify adhesive areas we used a semi-quantitative analysis [25] to distinguish between adherent and non-adherent areas within the projected cell area. To this end, we applied a threshold intensity corresponding to a cell-to-substrate distance of 40 nm [26]. Figures 3A & B show RICM images and respective threshold images of a representative PatuT and PatuS cell at different stages of cell spreading, namely 16, 30 and 60 min post plating.…”
Section: Cell Spreading Kineticsmentioning
confidence: 99%